2017
DOI: 10.26719/2017.23.7.507
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological characteristics and trends in the incidence of animal bites in Maku County, Islamic Republic of Iran, 2003-2012

Abstract: Caractéristiques et tendances épidémiologiques de l'incidence des morsures d'animaux dans la préfecture de Makou (République islamique d'Iran), 2003-2012RÉSUMÉ La présente étude a examiné les caractéristiques et l'incidence épidémiologiques dans le temps des morsures d'animaux dans la préfecture de Makou. Les données ont été obtenues à partir des registres de centres de santé portant sur les morsures d'animaux entre 2003 et 2012. Des informations sur les caractéristiques démographiques et les facteurs associés… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
2
2
0
Order By: Relevance
“…The time of year when the attack occurred was more reported in print than in the indexed and gray literature, which may also be due to the method of data collection. The higher number of bite incidents occurring in spring and summer, reported in the print media, coincides with previous scientific studies [4,47], which indicate that in these seasons, people engage in a higher number of outdoor activities, having a higher level of exposure and interaction with animals on public roads, predisposing them to possible attacks.…”
Section: Press Literaturesupporting
confidence: 88%
“…The time of year when the attack occurred was more reported in print than in the indexed and gray literature, which may also be due to the method of data collection. The higher number of bite incidents occurring in spring and summer, reported in the print media, coincides with previous scientific studies [4,47], which indicate that in these seasons, people engage in a higher number of outdoor activities, having a higher level of exposure and interaction with animals on public roads, predisposing them to possible attacks.…”
Section: Press Literaturesupporting
confidence: 88%
“…The findings of this study showed that men were more likely to suffer from animal bites than women (83.7%). In other investigations, gender distribution of animal bites was reported the same for example (Poorolajal et al, 2015) in the city of Tehran, (Kassiri et al, 2014b) in the city of (Shamshirgaran et al, 2017) in the city of Tehran in Iran illustrated that 84.5, 75.4 and 79.16% of animal bite cases had occurred in men and they achieved similar results in this respect. In a similar study in the southern of India, the proportion of men was reported by 72.4% (Taylor et al, 2017) which would be due to occupational exposure outside home and more contacts with risk factors (biting animals).…”
supporting
confidence: 55%
“…In the study conducted by (Babazadeh et al, 2016) in the city of Chaldoran in northwestern Iran, the incidence rate of animal bites was reported by 541 per 100,000 population. In another study in the city of Maku, Iran, the incidence rate was reported to be 250 per 100,000 individuals (Shamshirgaran et al, 2017). The reason for the lower incidence rate of animal bites in the county of Larestan compared to the overall average incidence rate in Iran and other regions could be attributable to lack of suitable vegetation and its warm and dry weather conditions in a way that the temperature could reach above 50°C in the summer which in turn could lead to an inappropriate habitat for the life of animals, especially wildlife.…”
mentioning
confidence: 97%
“…Several million dollars are spent annually on preventing rabies in Iran and no other contagious disease can be found in Iran that costs as much as rabies [14][15][16]. The growing trend of stray dogs populations and also increasing numbers of animal bite cases and rabies in many provinces of Iran, indicate the importance of paying more attention to their management and investigations on their different aspects [12,17]. Accurate information regarding the epidemiological status of the disease is needed for effective prevention programs [12,18].…”
Section: Introductionmentioning
confidence: 99%